Management of Refractory Orofacial Dyskinesia Caused by Anti-N-methyl-d-aspartate Receptor Encephalitis Using Botulinum Toxin - Zheng, Feixia; Ye, Xiuyun; Shi, Xulai; Poonit, Neha Devi; Lin, Zhongdong (Frontiers in Neurology, 2018)
The use of botulinum toxin type A (BoNT-A) injections for the treatment of orofacial dyskinesia secondary to anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is rarely reported. Here we report a case of an urgent, successful management of severe orofacial dyskinesia in an 8-year-old girl with anti-NMDAR encephalitis using BoNT-A injection. The patient presented with de novo unilateral paroxysmal movement disorder progressing to generalized dystonia and repetitive orofacial dyskinesia. Diagnosis was confirmed by the presence of NMDAR antibodies in serum and cerebrospinal fluid. The orofacial dyskinesia worsened despite the aggressive use of first-line immunotherapy and second-line immunotherapy (rituximab), and resulted in a potentially fatal self-inflicted oral injury. We urgently attempted symptomatic management using BoNT-A injections in the masseter, and induced muscle paralysis using vecuronium. The patient’s severe orofacial dyskinesia was controlled. We observed the effects of the BoNT-A injections and a tapering off of the effects of vecuronium ten days after the treatment. The movement disorder had improved significantly four weeks after the first administration of rituximab. The injection of BoNT-A into the masseter may be an effective treatment for medically refractory orofacial dyskinesia in pediatric patients with anti-NMDAR encephalitis. We propose that the use of BoNT-A injections should be considered early to avoid self-inflicted oral injury due to severe refractory orofacial dyskinesia in patients with anti-NMDAR encephalitis.